PENGABDIAN MASYARAKAT DENGAN PEMANFAATAN KAIN FLANEL DAN KAIN PERCA SEBAGAI PELATIHAN KREATIVITAS UMKM KERAJINAN TANGAN DI DESA SIUHOM - Handayani, Fitri Rahma; Nurdin, Hidayanti Rohimah (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
Micro, Small and Medium Enterprises (MSMEs) are part of the national business world which is recognized by the state and their existence is an important part in the context of improving the economy of the Indonesian people, both in small to larger scopes in various regions. Handicrafts are things related to handmade or activities related to goods produced through hand skills. The purpose of this service is to provide useful skills in making crafts from flannel and patchwork fabrics in order to increase the independence and creativity of children and young women in Siuhom Village. The method used by researchers is the ABCD approach which includes: Discovery, Design, Define, and Reflection. The results of these activities show a change in the children and Nauli Bulung Siuhom Village who are more creative and independent and the results of this UMKN are providing skills in making crafts from patchwork and flannel, providing skills that are useful for Nauli Bulung Siuhom Village and children Siuhom Village Elementary School by filling their spare time with positive and more useful things